Pengembangan Media Interaktif Materi Makna Proklamasi Pada Siswa Kelas Tinggi Sekolah Dasar - Shintya Mardania zufitri; Neni Hermita; Jesi Alexander Alim; Erlisnawati - (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Research aims to develop interactive learning media in elementary schools, especially on the material meaning of proclamation. This research is research and development by adopting 4D development model (Define, Design, Development, and Dissemination) put forward by Thiagarajan in 1974. Research and development involves media experts and material experts as expert validators to developed media. Data collection techniques in this study in the form of validity questionnaires and practicality. The data analysis technique used in this study is to calculate the average percentage of scores that can be seen from the aspects of appearance, material aspects (content), and practicality of respn teachers and students. The results obtained from the media validity test show that interactive media material meaning proclamations get a very valid category with a percentage score of 92%. The development of interactive media is said to be very valid because it meets the assessment criteria seen from the display, material, and language must be seen. While the results obtained from the practicality test of the response of students and teachers showed that interactive media material meaning proclamation is very practical with a percentage score of 90%. This shows that interactive media is worth using by teachers and students in learning. From the results of validity and practicality can be concluded that the interactive media material meaning proclamation in elementary school is declared very valid and very practical. This research is expected to help educators in using learning media in elementary schools, especially ips learning with the material meaning of proclamation, and can be a reference for other researchers in developing interactive learning media in elementary schools.